فقہِ جعفریہ کی روشنی میں ٹیسٹ ٹیوب بے بی اور اجارۂ رحم کا شرعی و اخلاقی جائزہ: A Jurisprudential and Ethical Analysis of Test-Tube Baby & Surrogacy in the Light of Ja‘fari Fiqh - Muhammad Abdullah; Dr. Abdul Ghaffar (Al-Amīr Research Journal for Islamic Studies, 2025)
This research paper presents an analytical study of In Vitro Fertilization (IVF), test-tube baby procedures, and surrogacy within the framework of Islamic jurisprudence, with special emphasis on the Ja‘fari school of thought. Modern reproductive technologies have enabled human intervention in the natural process of procreation; however, they have simultaneously raised profound ethical and legal questions concerning lineage (nasab), inheritance, sanctity, and chastity in Islamic law. The Ja‘fari jurisprudence, which regards both reason (‘aql) and revelation (naql) as valid sources of law, provides a rational yet principled approach to modern biomedical issues through the method of ijtihād bi al-maqāṣid (objective-based reasoning). This study critically examines the juristic opinions of eminent contemporary scholars such as Ayatollah Nāsir Makārim Shirazi, Ayatollah Rūḥullāh Khomeini, and Ayatollah Sayyid ‘Alī al-Sīstānī on assisted reproduction. The findings reveal that IVF is permissible only when both the sperm and ovum belong to legally wedded spouses and the embryo is implanted in the wife’s womb without the involvement of any third party. However, the use of a surrogate womb or gametes from non-spouses is considered prohibited (ḥarām) under Ja‘fari jurisprudence, as it leads to lineage confusion, moral ambiguity, and the commercialization of the human body. The paper concludes that assisted reproductive technologies can be harmonized with Islamic ethics only when they uphold the objectives of Sharī‘ah (Maqāṣid al-Sharī‘ah). namely the protection of lineage, dignity, and family integrity. Ja‘fari Fiqh thus provides a balanced, rational, and ethical framework that bridges the gap between modern science and religious principles. Keywords: Ja‘fari Jurisprudence, Islamic Bioethics, Test-Tube Baby, Lineage Preservation, Surrogacy, Makarim Shirazi; Rūḥullāh Khomeini.